KEPUASAN KERJA MEMEDIASI KEPEMIMPINAN TRANSFORMASIONAL DAN PEMBERDAYAAN TERHADAP KINERJA DOSEN (Studi Kasus Politeknik Ilmu Pelayaran Semarang) - 11.52.02.0089, Arika Palapa (Jurnal Mahasiswa Pasca Sarjana, 2013)
The purpose of this study is to examine the effect of Transformational leadership and empowerment on performance, moderated by the job satisfaction in Marine Polytechnic State of Semarang.The population of this study is 98 Lecturer of Polytechnic State of Semarang. Analysis of the data was using linear regression The result of this study find that the transformational leadership is affect in job satisfaction, the empowerment is affect in job satisfaction, the transformational leadership is affect the performance of lecturers, the empowerment is effect on the performance of lectures, the job satisfaction is effect on the performance of lecturer, the job satisfaction does not mediate the transformational leadership to the performance of lecturer because the indirect effect is smaller than the direct affect and job satisfaction does not mediate the empowerment to the performance of lecturers because the indirect effect is smaller than the direct affect. Key words: Transformational Leadership, Empowerment, Job satisfaction and Performance of lecturer